J-102 Decreased levels of seroreactivity in individuals subjected to antiretroviral therapy early in acute HIV infection. (April 2018) - Manak, Mark; Shutt, Ashley; Eller, Leigh; Robb, Merlin; Jagodzinski, Linda; Ananworanich, Jintanat; Peel, Sheila
Abstract : WHO guidelines recommend antiretroviral treatment (ART) of all HIV infected individuals regardless of CD4 count. Early treatment minimizes the risk of HIV transmission, lowers the natural reservoir of the virus, and reduces subsequent serious AIDS related events, but may also disrupt emergence of HIV diagnostic markers. High-risk individuals at early stages of HIV infection, (HIV-1 RNA positive, Western Blot negative or indeterminate), were enrolled into an IRB approved study to examine the outcomes of early HAART initiation. Plasma samples collected at week 0, 2, 12, and 24 were tested by EIA 1/2 Plus O, HIV-1/2 Ag/Ab Combo, HIV-1/2 MultiSpot (MS), and HIV-1 Western Blot (WB) (all from Bio-Rad, Redmond, WA). HIV Viral Load was determined by Abbott m2000 HIV-1 RT PCR (Chicago, IL). Stage of HIV infection was based on the Fiebig staging system. Of individuals treated at Fiebig I and II, 63.6 and 59.1%, respectively, were antibody negative at 12 weeks. At week 12, MS was reactive in 18.2%, 53.7% and 35.0% of individuals treated at Fiebig I, II, and Fiebig III/IV, and decreased to 9.1%, 48.4% and 30.0%, respectively, by week 24. 52.9% of individuals treated at Fiebig III/IV were negative at week 24. In contrast, all untreated individuals were highly reactive by EIA, WB, MS and RNA by week 2–3 after infection and remained reactive thereafter. Absence of serological markers in individuals treated early in infection presents challenges in determining status of infection, as some individuals under therapy may test serologically non-reactive and RNA negative, but are infected. These findings may also have implications in monitoring individuals on Pre-exposure Prophylactics (PrEP) by serological tests alone.